The Power of the Symposium: Impacts from Students' Perspectives - Diana Vanek; Nancy Marra; Carolyn Hester; Desirae Ware; Andrij Holian; Tony Ward; Randy Knuth; Earle Adams (The Rural Educator, 2011)
The Air Toxics under the Big Sky program developed at the University of Montana is a regional outreach and education initiative that offers a yearlong exploration of air quality and its relation to respiratory health. The program was designed to connect university staff and resources with rural schools enabling students to learn and apply science process skills through self-designed research projects conducted within their communities. As part of the program, students develop and conduct independent projects, then share their findings at the conclusion of the school year in some type of interactive capstone experience, the most prominent being a high school symposium held at The University of Montana campus. Student feedback collected through a carefully controlled evaluation program suggest that the annual symposium as the culminating event is a critical component of the Air Toxics Under the Big Sky program, and a valuable learning experience as many of the students go on to post-secondary education.